2023
DOI: 10.3389/fcimb.2023.1092317
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathways that permit Mycobacterium avium subsp. hominissuis to transition to different environments encountered within the host during infection

Abstract: IntroductionM. avium subsp. hominissuis (M. avium) is an intracellular, facultative bacterium known to colonize and infect the human host through ingestion or respiratory inhalation. The majority of pulmonary infections occur in association with pre- existing lung diseases, such as bronchiectasis, cystic fibrosis, or chronic obstructive pulmonary disease. M. avium is also acquired by the gastrointestinal route in immunocompromised individuals such as human immunodeficiency virus HIV-1 patients leading to disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Host-derived fatty acids are important carbon sources for mycobacteria inside host macrophages [ 68 70 ]. Previous studies have reported that fatty acid pathways are enriched in host-mimicking environments, including nutrient starvation and biofilm conditions, and are associated with antibiotic susceptibility [ 71 , 72 ]. Thus, inhibition of fatty acid synthesis by PTM may effectively eliminate the SCV phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Host-derived fatty acids are important carbon sources for mycobacteria inside host macrophages [ 68 70 ]. Previous studies have reported that fatty acid pathways are enriched in host-mimicking environments, including nutrient starvation and biofilm conditions, and are associated with antibiotic susceptibility [ 71 , 72 ]. Thus, inhibition of fatty acid synthesis by PTM may effectively eliminate the SCV phenotype.…”
Section: Discussionmentioning
confidence: 99%